EConsults' Impact on Care Access and Wait Times in Rheumatology. Issue 3 (24th April 2022) - Malcolm, Elizabeth J.; Brandon, Zachary; Wilson, Lauren E.; Shoup, John Paul; King, Heather A.; Lewinski, Allison; Greiner, Melissa A.; Malone, Shauna; Miller, Julie; Keenan, Robert T.; Tarrant, Teresa K.; Phinney, Donna; et al.
Abstract : Background/Objective: A growing number of health systems have implemented eConsults to improve access to specialty advice, but few studies have described their use in rheumatology or impact on visit wait times. We evaluated the uptake of an eConsult program and its impact on wait times for in-person rheumatology visits. Methods: In this quality improvement project, we analyzed electronic health record data from 4 intervention clinics and 4 comparison clinics, 12 months before and after implementation of an eConsult program. We compared median wait time for rheumatology appointments using a pre-post difference-in-differences analysis and quantile regression, adjusting for patient age, race, sex, clinic pair, and primary insurance payer. We also interviewed 11 primary care providers from the intervention clinics and conducted a rheumatology provider focus group (n = 4) to elucidate experiences with the program. Results: Rheumatologists recommended management in primary care or referral to another specialty for 41% of eConsults, reducing initial demand for in-person visits. The median wait times dropped in the intervention and the comparison clinics (42 and 25 days, respectively). Intervention clinic median wait time dropped 17 days more than comparison clinics, and this was nonstatistically significant ( p = 0.089). eConsults fit provider care tasks best for triage or initial workup for diagnosis, and less well when tests required interpretation, or when back and forth communication was needed to manage the patient's condition. Conclusions: Implementation of eConsults for rheumatology was associated with reduced wait times for rheumatology appointments and supported primary care providers in the triage and workup for a substantial portion of patients.